Survey on the tribe Tigridieae (Iridaceae) in the Campos of Southeast South America - Deble, Leonardo Paz (Balduinia, 2022)
Survey on the tribe Tigridieae (Iridaceae) in the Campos of Southeast South America (SESA Grasslands). Iridaceae is one of the largest families of monocots and is an important constituent of grassland ecosystems across the globe. The tribe Tigridieae is exclusive to the Americas, with an important center of diversity in the Andean region, in the Campos of Southeast South America, in Mexico and in the southern United States. In this study, a survey of the Iridaceae-Tigridieae native to the Grassland Ecosystems of Southeast South America (=SESA Grasslands) is carried out. The SESA was divided into four regions: Campos, Campos de Altitude, Chaco Húmedo and Pampa. The Iridaceae-Tigridieae are represented by a total of 65 species (including ten subspecies), distributed in ten genera. The genus Cypella with 30 species and eight subspecies is the most diverse, followed by Calydorea (13 species), Herbertia (11 species) and Gelasine (four species and two subspecies). A total of 87% of the taxa occurring in the SESA are endemic, most of them exclusive to the Campos region, which includes 54 taxonomic entities, of which 41 taxa are endemic The Campos de Altitude region is represented by 15 taxa, including six endemic species. The Pampa region includes six taxonomic entities, being one of them endemic. The Chaco Húmedo region comprises five species, none of which are exclusive to the latter region. Key words: Bulbous, Grasslands, High Grasslands, Humid Chaco, Geographic distribution, diversity, Pampa.